Physicochemical Treatment of Hazardous Wastes - Tang, Walter Z. (CRC Press, 2009)
On average, one ton of hazardous waste per person is generated annually by industries in the United States. Before the Resource Conservation and Recovery Act of 1984, hazardous wastes were improperly disposed of into the environment without any regulation. As a result, remediation of these contaminated sites and management of the ongoing hazardous waste sources are two major tasks to be achieved by treatment technologies. Due to the complex nature of the contaminated media and of the pollutants, environmental professionals are facing a host of questions, such as: What are the contaminated media? What is the nature of the pollutants? What are the concentrations of each pollutant? Among biological, physicochemical, or thermal technologies, if physicochemical processes are to be the solution, the treatability of various pollutants must be assessed before a process can be properly designed. This book systematically examines the treatability of hazardous wastes by various physicochemical treatment processes according to the Quantitative Structure–Activity Relationships (QSARs) between kinetic rate constants and molecular descriptors.